Augmented Reality–Based Flashcard Media: A Study of Foster Senior High School Students’ Critical Thinking Skills on Atomic Models - Anggraini, Riska; Marlina, Leni; Siahaan, Sardianto Markos (Integrated Science Education Journal, 2026)
Purpose of the study: This study aimed to develop augmented reality–based flashcard learning media for teaching atomic models and to examine its validity, practicality, and effectiveness in fostering senior high school students’ critical thinking skills. Methodology: This study employed a research and development approach using the Rowntree model, comprising planning, development, and evaluation stages, with formative evaluation adapted from Tessmer. Data were collected through expert validation sheets, practicality questionnaires, and critical thinking skills tests. Data analysis included CVR and CVI for validity, descriptive analysis for practicality, and N-gain analysis for effectiveness. Main Findings: The results indicated that the augmented reality–based flashcard media achieved excellent content validity, with S-CVI/Ave and S-CVI/UA values of 1.00, categorized as very valid. The media was considered practical, with mean practicality scores of 3.9 in the one-to-one evaluation and 4.1 in the small group evaluation. Additionally, the field test showed an improvement in students’ critical thinking skills, with an N-gain value of 0.56, indicating moderate effectiveness. Novelty/Originality of this study: The novelty of this study lies in integrating augmented reality technology into flashcard-based learning media to foster students’ critical thinking skills in learning atomic models. Unlike previous studies that mainly emphasize visualization or conceptual understanding, this research focuses on developing higher-order thinking skills through interactive, mobile-supported learning media to address abstract physics concepts.